Limitações da utilização do equivalente metabólico (MET) para estimativa do gasto energético em atividades físicas - Crisp, Alex Harley [UNESP]; Verlengia, Rozangela; Oliveira, Maria Rita Marques de [UNESP] (My University, 2014)
Determining the total energy expenditure is extremely important in the field of health sciences, with the voluntary physical activity the most variable component. This work contextualizes metabolic equivalent (MET), a simple and practical method for estimating the energy expenditure of exercise and physical activity in adults. The MET is based on the resting oxygen consumption value of 3.5 mL/kg/min, but the exact origin of this value is unknown. In contrast, studies in heterogeneous and specific populations (i. e. obese, elderly) show lower values than the default value. Consequently, the energy expenditure in voluntary physical activity may be underestimated, since they are based in the elevation (multiples) of oxygen consumption when compared to the resting state. In this context, recent studies suggest a correction of the value of 1 MET through the Harris-Benedict equation (3.5 ÷ estimated resting metabolic rate [mL/kg/min]), provides a more individualized and accurate estimation of the energy expenditure directly measured (indirect calorimetry). This factor can favor the better planning of nutritional interventions and physical training. Calculations and estimates are always subject to errors due to physical/biological variations among individuals and environmental factors. This factor can favor the better planning of nutritional interventions and physical training. However, does not justify the use of a universal value (1 MET = 3.5 mL/kg/min) for entire population, which results in inadequate estimates of energy expenditure in physical activities. On the other hand, new studies must be carried out so that correction factors may be proposed for specific populations, given that are also controversies between the predictive equations of resting metabolic rate.

A determinação do gasto energético total é de extrema importância na área da saúde, com as atividades físicas voluntárias o componente mais variável. O presente texto contextualiza equivalente metabólico (MET), metodologia considerada simples e prática para a estimativa do gasto energético de exercícios e atividades físicas em adultos. O MET baseado no valor de consumo de oxigênio em repouso de 3,5 mL/kg/min, mas a origem exata desse valor não é conhecida. Em contrapartida, estudos em populações heterogêneas e específicas (obesos, idosos) mostram valores menores desse valor padrão. Como consequência, o gasto energético em atividades físicas voluntárias pode ser subestimado, uma vez que a estimativa é baseada na elevação (múltiplos) do consumo de oxigênio em relação ao estado de repouso. Nesse contexto, recentes estudos sugerem que a correção do valor de 1 MET por meio da equação de HarrisBenedict (3,5 ÷ Taxa metabólica de repouso estimada [mL/kg/min]), fornece uma estimativa mais individualizada e próxima do gasto energético mensurado diretamente (calorimetria indireta). Fator que pode favorecer um melhor planejamento de intervenções nutricionais e treinamento físico. Cálculos e estimativas sempre estarão sujeitos a erros devido às variações físicas/biológicas entre indivíduos e fatores ambientais. No entanto, não se justifica a utilização de um valor universal (1 MET = 3,5 mL/kg/min) para toda a população, no qual resulta em estimativas inadequadas do gasto energético em atividades físicas. Por outro lado, novos estudos devem ser realizados para que fatores de correção possam ser propostos em populações específicas, uma vez que também existem controvérsias entre as equações preditivas da taxa metabólica de repouso.
Limitations of using the metabolic equivalent (MET) to estimate energy expenditure in physical activities
Keywords: Metabolic equivalent; Energy expenditure; Physical activity; Equivalente metabólico; Gasto energético; Atividades físicas